Komunikasi Politik Muhammad Al-Fatih Dalam Menaklukan Konstantinopel - Syalva Witria; Rasyidah; Mirza Adia Nova; Fathayatul Husna (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Sultan Muhammad Al-Fatih's political communications became in the public spotlight, when he was able to make an Islamic history known to the world with his success in conquering the city of Constantinople. From his figure who is smart, hard, committed and courageous, it becomes the capital to prove the bisyarah of Rasulullah SAW. However, of course this is not enough, the Sultan must be able to win the hearts of and mobilize the Muslims to jointly fight and conquer the city of Constantinople. This research is historical research using qualitative methods with library research and historical approach techniques. The results of this study indicate that during his leadership period Sultan Muhammad Al-Fatih implemented policies based on Islamic law, including reforming the government system, upholding Islamic leadership, upholding justice and moral values, and giving freedom to Christians and Jews in worship with certain conditions. The Sultan uses language properly and precisely in conveying the rules that apply during his leadership. both in the form of information, education and instructions, so as to form the mentality and enthusiasm to prove the bisyarah of the Prophet Muhammad, jihad fi sabilillah and get the title of ghazi.